New Benzimidazoles Targeting Breast Cancer: Synthesis, Pin1 Inhibition, 2D NMR Binding, and Computational Studies - Nashaat, Samira; Henen, Morkos A.; El-Messery, Shahenda M.; Eisa, Hassan (Molecules (Basel, Switzerland), 2022)
Benzimidazole derivatives are known to be key players in the development of novel anticancer agents. Herein, we aimed to synthesize novel derivatives to target breast cancer. A new series of benzimidazole derivatives conjugated with either six- and five-membered heterocyclic ring or pyrazanobenzimidazoles and pyridobenzimidazole linkers were synthesized yielding compounds 5–8 and 10–14, respectively. Structure elucidation of the newly synthesized compounds was achieved through microanalytical analyses and different spectroscopic techniques (1H, 13C-APT and 1H–1H COSY and IR) in addition to mass spectrometry. A biological study for the newly synthesized compounds was performed against breast cancer cell lines (MCF-7), and the most active compounds were further subjected to normal Human lung fibroblast (WI38) which indicates their safety. It was found that most of them exhibit high cytotoxic activity against breast cancer (MCF-7) and low cytotoxic activity against normal (WI38) cell lines. Compounds 5, 8, and 12, which possess the highest anti-breast cancer activity against the MCF-7 cell line, were selected for Pin1 inhibition assay using tannic acid as a reference drug control. Compound 8 was examined for its effect on cell cycle progression and its ability to apoptosis induction. Mechanistic evaluation of apoptosis induction was demonstrated by triggering intrinsic apoptotic pathways via inducing ROS accumulation, increasing Bax, decreasing Bcl-2, and activation of caspases 6, 7, and 9. Binding to 15N-labeled Pin1 enzyme was performed using state-of-the-art 15N–1H HSQC NMR experiments to describe targeting breast cancer on a molecular level. In conclusion, the NMR results demonstrated chemical shift perturbation (peak shifting or peak disappearance) upon adding compound 12 indicating potential binding. Molecular docking using ‘Molecular Operating Environment’ software was extremely useful to elucidate the binding mode of active derivatives via hydrogen bonding.